Айболит - Чуковский Корней Иванович (Для самых маленьких, 2001)
Экземпляры: ф.13 (20181126) / Инвентарный номер: 50700 / Цена: 30.00 / Сис.шифр: Д / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6